Investigating the effectiveness of using a telemental health approach to manage obsessive-compulsive disorder: a systematic review - Zahra Karbasi; Parisa Eslami; Azam Sabahi; Maryam Zahmatkeshan (Middle East Current Psychiatry)
Abstract Background Obsessive-compulsive disorder is a mental disorder that leads to impairment in various cognitive functions. Telemental health is applied in providing several telemental health and psychiatric services. It can provide health and psychological care, such as counseling, diagnosis, and treatment. Therefore, this study systematically examines the effectiveness of using a telemental health approach to manage obsessive-compulsive disorder. Methods We searched PubMed, Web of Science, and Scopus using the keywords telepsychiatry, telemental health, telemedicine, telehealth, videoconferencing, obsessive-compulsive disorder, and OCD up to November 2023. In addition to searching the mentioned databases, references to related articles were also examined. Results In this study, based on the search strategy, we identified 130 articles, 4 duplicate articles were removed, and the title and abstract of 126 articles were reviewed. Considering the selection criteria, 104 articles were excluded and 22 articles were included in the study. In 77.27% of the articles, videoconference telecommunication methods were used for communication. In 8 articles, the participants were children and adolescents. Reviewing these studies indicates mentions concerning the effectiveness of this method in most of them. Conclusions In general, telemental health interventions increase access to treatment and can be promising for patients with certain conditions. This systematic review contributes to the expanding literature indicating that delivering CBT through telemental health methods, particularly videoconference-based approaches, is a feasible substitute for in-person treatments.